Kajian kelakuan pasir penyambung turapan penguncian blok konkrit pada jarak sambungan dan kecerunan yang berbeza - Md.Yusoff, Nur Izzi (2005)
This study sought to determine the performance of jointing sand of interlocking concrete block pavement (ICBP) under different joint widths and slope. Laboratory scale model (1.20 x 0.60 m) was developed to study on these parameters. Concrete blocks (quadpave) of 200 mm x 100 mm x 60 mm were used as a surface layer. The width of the joint between pavers used for test varied from 2 mm, 4 mm, and 6 mm and different slopes 0% to 5%, 10% and 15%. From study, the sand used did not exceed the limitations regarding to the CCAA (1986) gradation specifications. It also found that the average moisture content of 7.38 % was in acceptable range. The value of coefficient of permeability k was found to be 0.03 mm/s, which shows poor drainage ability of the sand. Summarizing this, mainly the rounded quartz river sand was suitable to be used as jointing and bedding sand as observed in the test. Based on the study also indicated that 2 mm joint width was suitable to be used for the steep road. From the data obtained, it indicated that when the joint width increased, interlock behaviour of the pavement decreased. This result is supported by the pull out test, only small forces needed to pull the pavers out from it place. When this condition occurred, the interlock behaviour reduced and exposed to the friction between pavers. The absence of water in a small amount help the jointing sand compressed but greater in its amount caused sand erosion especially at steeper slope. Results showed that the water eroded the higher degrees of slopes, more sand. Based on limited results from the study, ICBP road must not exceed 10% slope to avoid the sand erosion from the joints and decrease of interlock behaviour between the pavers.